Dewatering of pulp and paper mill biosludge and primary sludge. Issue 5 (October 2018) - Meyer, Torsten; Amin, Parthiv; Allen, D. Grant; Tran, Honghi
Abstract: Dewatering and handling of pulp and paper mill sludge is challenging and often comprises more than half of the overall wastewater treatment costs at a mill. Primary sludge is usually more dewaterable than biosludge (waste activated sludge), and the ratio between both types of sludge largely determines the dewaterability of the sludge mix. This study has quantified the benefits of adding primary sludge to biosludge to enhance the dewaterability in terms of cake solids and filtrate/pressate solids content. Furthermore, the effects of the particle size distribution and the monovalent to divalent cation ratio of the various types of sludge were investigated. Biosludge and three types of primary sludge from a Canadian pulp and paper mill were mixed at various ratios and tested for dewaterability using a Crown Press®, a bench-scale device which simulates industrial belt press dewatering. Results show that after addition of primary sludge at up to 40% mass proportion (dry solids basis) the dewatered cake solids content increased substantially, from 10.4% to 18.7–19.9%, depending on the type of primary sludge added. Further addition of primary sludge led to comparably only small improvements. Primary sludge addition also resulted in decreased total suspended solids (TSS) concentrations in the combined gravity filtrate / Crown Press pressate. Primary sludge content of only 10% in the sludge mix was sufficient to decrease the TSS concentration from 1.8  g /L to 0.2 – 0.4  g /L. The study shows that only less than half of the sludge mix needs to consist of primary sludge, in order to achieve adequate dewaterability. This opens up the possibility of retaining more primary fiber within the pulping process, without compromising downstream sludge dewatering.